PERILAKU MASYARAKAT DALAM PENGELOLAAN SAMPAH DAN FAKTOR-FAKTOR YANG MEMPENGARUHI DI KECAMATAN DENPASAR TIMUR KOTA DENPASAR, PROVINSI BALI - Sukerti, Ni Luh Gede; Sudarma, I Made; Pujaastawa, I.B.G (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 11 No 2 (2017), 2017)
ABSTRACT          Waste problem is one of the environmental issues that have long been the world's attention and need to get serious handling so as not to cause harmful impacts. Community behavior is the most important variable in waste management and its success should be supported by a high level of public awareness. The factors that can affect the behavior of society, including internal factors and external factors. The purpose of this research is to know the behavior of society in waste management, to know the relation of internal factor and external factor in waste management in East Denpasar Subdistrict.        The design of this study included cross sectional with stratified random sampling. The sample in this research is housewife who lives and settles and has (KTP) East Denpasar, as many as 100 respondents. The data collected in this research are the respondent's characteristic, respondent's behavior, internal and external factors and the factors driving the participation in waste management. The data is obtained then analyzed using SEM-PLS data analysis with the help of Smart PLS software.        Based on the results of SEM-PLS analysis show that from nine behavioral indicators in managing the waste studied found the result that the behavior of sorting organic and inorganic waste has the highest value to the behavior of the community in managing waste. The internal factor variables indicate that people's knowledge has the highest value in managing waste from the four indicators studied, while external factor variables show that law enforcement has the highest value of three meticulous indicators on the behavior of the community in managing waste in East Denpasar Subdistrict.        The conclusion of this research shows that there is a relationship between the behavior of managing waste with internal and external factors. Community behavior in sorting organic and inorganic waste in the category of good because it is supported by knowledge and awareness of good society in managing waste and by obeying the rules in disposing garbage.   Keywords: Community behavior; Waste management;